2012
DOI: 10.1016/j.jval.2011.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Switching Patients with Type 2 Diabetes from Insulin Glargine to Insulin Detemir in Chinese Setting: A Health Economic Model Based on the PREDICTIVE Study

Abstract: Conversion to IDet from an IGla regimen improved life expectancy and was a cost-saving treatment approach in a Chinese setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…The improvements in glycemic control observed in the current study conflict with results from the PREDICTIVE trial [13, 14] but are consistent with those from two US studies [15, 16]. In our study, the treatment persistence rate was significantly higher in the GLA-C group and medication adherence was significantly higher among GLA-S patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The improvements in glycemic control observed in the current study conflict with results from the PREDICTIVE trial [13, 14] but are consistent with those from two US studies [15, 16]. In our study, the treatment persistence rate was significantly higher in the GLA-C group and medication adherence was significantly higher among GLA-S patients.…”
Section: Discussionsupporting
confidence: 89%
“…In a European cohort of patients ( n  = 777) in the PREDICTIVE study, there were significant improvements in HbA 1c with fewer hypoglycemic events after switching to insulin detemir [13]. Using the framework of cost-effectiveness analysis, an Asian study based on data from a Korean cohort of the PREDICTIVE study reported reduced total diabetes care costs and increased life expectancy of 0.06 years after switching from insulin glargine to insulin detemir [14]. A small retrospective study recently evaluated outcomes in patients ( n  = 10 with type 1 diabetes and n  = 21 with T2DM) switching from insulin glargine to insulin detemir due to changes in Medicaid formulary coverage [15].…”
Section: Introductionmentioning
confidence: 99%
“…A key advantage of the present analysis is the simplicity and transparency of the model used to evaluate cost-utility. The majority of published cost-utility analyses of both type 1 and type 2 diabetes interventions have taken a long-term perspective, evaluating clinical and cost outcomes over patient lifetimes [32][33][34][35] . A long-term modeling approach is consistent with the progression of diabetes, with diabetesrelated complications in the future having a significant impact on quality-of-life and medical costs.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed calculation methods are presented in Appendix S5 and Appendix S6. The cost data missed in the CHIRA database were derived from other Chinese literature …”
Section: Methodsmentioning
confidence: 99%